EFFECTIVELY EXPLOIT SPECIALTIES OF THE CENTRAL HIGHLANDS REGION OF VIETNAM AND POTENTIAL UTILIZE BY-PRODUCTS TO CREATE VALUE-ADDED PRODUCTS - Thuy, Nguyen Minh; Hao, Hong Van; Giau, Tran Ngoc; Minh, Vo Quang; Tai, Ngo Van (My University, 2025)
The Central Highlands is a key agricultural production region of Vietnam with many high-value export agricultural products such as coffee, pepper, rubber, and valuable fruits such as avocado, durian, and passion fruit, and some other agricultural products. However, the commercial value of edible agricultural products for human consumption is limited due to lack of attention to storage and processing conditions. Therefore, applying and investing in advanced preservation and processing techniques suitable for available raw materials in the Central Highlands is a highly feasible activity. Recent studies from international and domestic researchers showed various application could apply, which were presented in this paper including irradiation technology, steam/hot water treatment technology, zeolite technology, cold/cold storage technology combined with controlled atmosphere storage. When these activities are successful, it would reduce post-harvest loss of agricultural products, meeting the demand for food for the whole country and for export. For high nutritional value raw materials, it is necessary to invest more in potential preservation, processing, and utilization of waste by-products to increase diversity, improve quality, and ensure food hygiene and safety value-added products. The utilization of waste from agricultural product also was well-known that suitable for Sustainable Development Goals of United Nations. The quality of input materials and output products must be strictly controlled when applying advanced technology. This activity was controlled, that would ensure the safety of processed products, creating good conditions for the national and global agricultural value chain. Thanks to that, effectively taking advantage of the region's specialties and food processing is no longer a weakness of Central Highlands agricultural products in Vietnam, making an important contribution to the socio-economic development and stability of the region and the whole country.
Keywords: Agricultural products; Central Highlands; Diversification; Food Preservation; Food processing